2, 3-Dihydrobenzofuran privileged structures as new bioinspired lead compounds for the design of mPGES-1 inhibitors. Issue 4 (15th February 2016) - Di Micco, Simone; Spatafora, Carmela; Cardullo, Nunzio; Riccio, Raffaele; Fischer, Katrin; Pergola, Carlo; Koeberle, Andreas; Werz, Oliver; Chalal, Malik; Vervandier-Fasseur, Dominique; Tringali, Corrado; Bifulco, Giuseppe
Graphical abstract: Abstract: 2, 3-Dihydrobenzofurans are proposed as privileged structures and used as chemical platform to design small compound libraries. By combining molecular docking calculations and experimental verification of biochemical interference, we selected some potential inhibitors of microsomal prostaglandin E2 synthase (mPGES)-1. Starting from low affinity natural product1, by our combined approach we identified the compounds19 and20 with biological activity in the low micromolar range. Our data suggest that the 2, 3-dihydrobenzofuran derivatives might be suitable bioinspired lead compounds for development of new generation mPGES-1 inhibitors with increased affinity.